C1-inhibitor reduces hepatic leukocyte-endothelial interaction and the expression of VCAM-1 in LPS-induced sepsis in the rat - Croner, Roland; Lehmann, Thorsten G.; Fallsehr, Christine; Herfarth, Christian; Klar, Ernst; Kirschfink, Michael (Microvascular research, 2004)
INTRODUCTION: Increased leukocyte-endothelial interaction (LEI) leading to hepatic microperfusion disorders is proposed as major contributor for hepatic failure during sepsis. Recently it has been demonstrated that complement inhibition by C1-inhibitor (C1-INH) is an effective treatment against microcirculatory disturbances in various diseases. The purpose of this study was to investigate the influence of C1-INH on microcirculation and LEI in the liver in a rat model of sepsis. MATERIALS AND METHODS: Rats received lipopolysaccharides (LPS) from Escherichia coli intravenously. Controls received Ringer solution only. Ninety minutes after LPS infusion some animals were treated with C1-INH intravenously (LPS + C1-INH). Others (LPS + SC) and controls (Ringer + SC) received sodium chloride (SC). Hepatic LEI and mean erythrocyte velocity (MEV) were quantified by intravital microscopy (IVM) 90 min after LPS or Ringer infusion (0) and 30, 60, 90 and 120 min following treatment. VCAM-1 m-RNA in hepatic tissue, C3a, TNF-alpha and hepatic enzyme liberation in blood was analysed. RESULTS: Leukocyte sticking to the endothelial wall in postsinusoidal venules was significantly reduced in the LPS + C1-INH vs. the LPS + SC group 30, 60, 90 and 120 min after treatment. VCAM-1 m-RNA expression in the hepatic tissue was markedly and C3a levels in plasma were significantly reduced in the LPS + C1-INH vs. the LPS + SC group. No differences in TNF-alpha levels were detected between these two groups. MEV was improved in the LPS + C1-INH vs. the LPS + SC group. CONCLUSIONS: Our results indicate that even upon delayed treatment hepatic adhesion molecule expression and LEI can be reduced by C1-INH. The multifunctional regulator may reduce hepatic microcirculatory disturbances during sepsis under clinical conditions.
Gesehen am 15.02.2021